Method for preparing high-performance antibacterial degradable PBAT-based composite film based on two-way stretching technology

Biaxial stretching of a PBAT/PLA composite film with minimal additives enhances mechanical and antibacterial properties, addressing compatibility issues and improving film performance for packaging applications.

CN119161611APending Publication Date: 2024-12-20CHENGDU PUMIYI TECH CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411137821.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

PBAT films exhibit low mechanical strength, poor dimensional stability, and inadequate gas barrier properties, and the introduction of antibacterial agents compromises mechanical properties, limiting their application in packaging and other fields.

Method used

A method involving biaxial stretching of a PBAT/PLA composite film with a small amount of cross-linking agent (DCP) and glycerol to enhance compatibility, combined with selective use of commercial antibacterial agents like polyhexamethyleneguanidine hydrochloride, ε-polylysine hydrochloride, or nisin, to improve mechanical and antibacterial properties without significant deterioration.

Benefits of technology

The method results in a composite film with enhanced mechanical properties, improved gas barrier, and high antibacterial efficacy against Staphylococcus aureus and Escherichia coli, with potential for industrial use in green packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161611A_ABST
    Figure CN119161611A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a high-performance antibacterial degradable PBAT-based composite film based on a two-way stretching technology, which comprises the following steps: mixing 70-80 parts of PBAT, 20-30 parts of PLA, 0.05-0.15 part of dicumyl peroxide, 3-5 parts of glycerol and 0.5-3 parts of a commercial antibacterial agent, and sequentially carrying out banburying, dicing, hot die casting and two-way stretching to obtain the high-performance antibacterial degradable PBAT-based composite film. According to the method, the compatibility of the PBAT / PLA blending system is improved, and meanwhile, a smaller amount of processing aid is added on the basis of not influencing the mechanical property, so that various properties of the prepared film product are further improved, and the advantages of the PBAT / PLA blending system are brought into play; meanwhile, through selective addition of a smaller amount of commercial antibacterial agent, the antibacterial rate of staphylococcus aureus can reach 99%, and the antibacterial rate of escherichia coli can reach 100% on the premise of a smaller addition amount.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of PBAT-based composite film materials, and relates to a method for preparing a high-performance antibacterial and degradable PBAT-based composite film based on a biaxial stretching technology, and specifically relates to preparing a biodegradable PBAT / PLA composite film with high mechanical properties, low oxygen permeability coefficient, high heat sealing strength, high heat shrinkage rate and high antibacterial properties. Background Art

[0002] In recent years, with the gradual implementation of national policies and the improvement of people's environmental awareness, biodegradable materials represented by PBAT have received widespread attention. Good biodegradability is conducive to its decomposition by microorganisms in the natural environment, and finally converted into carbon dioxide and water, which is environmentally friendly and solves the "white pollution" problem from the source. The PBAT molecular chain has good flexibility, excellent material toughness, strong impact resistance, good ductility, and good film-forming properties, making it an ideal material for making film products. In addition, PBAT has good plasticity and processability. PBAT products also have good mechanical properties and thermal stability during use. They are widely used in packaging, medical, agriculture, textiles, and disposable products. PBAT has become one of the most commercially promising materials and is expected to replace traditional plastics. Film products occupy an important part in people's daily lives. PBAT film products have the advantages of good gloss and high flexibility. They are a type of product with great potential and can be used in food packaging, electronic product packaging, agriculture and medical fields. PBAT film products have good flexibility, but low mechanical strength, poor dimensional stability, and gas barrier properties need to be improved, which makes it difficult to meet the actual packaging film application needs. Therefore, the enhancement and modification of PBAT film has become a research hotspot. The material microstructure, molecular chain orientation, crystallinity, etc. can be adjusted by blending with other high-strength biodegradable materials and applying external fields to improve the overall performance of the film.

[0003] PLA is mature in industrialization and low in price, making it an ideal blending reinforcement modifier for PBAT. However, due to the poor compatibility between PLA and PBAT, the domain size is large, the interface adhesion is weak, the toughening efficiency is low, and the mechanical properties of the blended materials and film products are poor. At the same time, in the prior art, most people choose to prepare high-performance biodegradable materials by blending PLA as the main component with a small amount of PBAT. Reports on blending systems with PBAT as the main component are relatively rare. However, for film products, PBAT as a matrix can often better meet the toughness requirements.

[0004] In industry, PBAT films are often produced by the blown film method. The thickness of the products produced is often difficult to control, and the tensile strength is difficult to reach the ideal level. In addition, the temperature resistance and dimensional stability of PBAT films need to be improved.

[0005] At the same time, in the actual application scenarios of PBAT film, it is used as a commodity packaging film by people in their daily lives, so it usually carries a large number of harmful or even pathogenic bacteria. Compared with PBAT film, it is more difficult to introduce antibacterial agents into the PBAT / PLA blend system due to the incompatibility of the system. When a standard content (10wt%) of commercial antibacterial agents is introduced to maintain its antibacterial properties, the mechanical properties of the PBAT / PLA composite film will be significantly reduced. The same problem also exists in the processing aids commonly used in the preparation of PBAT / PLA blend system materials.

[0006] Therefore, if a biodegradable PBAT / PLA composite film material can be invented that can fully utilize the mechanical properties advantages of the PBAT / PLA blend system and has high antibacterial functionality, this will provide a broader market prospect and development space for new packaging film materials. Summary of the invention

[0007] The purpose of the present invention is to solve the problems in the above-mentioned background technology and provide a method for preparing a high-performance antibacterial and degradable PBAT-based composite film based on biaxial stretching technology. The method realizes that while the PBAT / PLA blending system improves the compatibility, a smaller amount of processing aids is added without affecting the mechanical properties, so as to further improve the various properties of the prepared film products and give full play to the advantages of the PBAT / PLA blending system; at the same time, through the selective addition of a smaller amount of commercial antibacterial agent, the antibacterial rate of Staphylococcus aureus can reach 99%, and the antibacterial rate of Escherichia coli can reach 100% under the premise of a smaller amount of addition.

[0008] To achieve the above objectives, the present invention is implemented by adopting a technical solution consisting of the following technical measures.

[0009] A method for preparing a high-performance antibacterial and degradable PBAT-based composite film based on biaxial stretching technology comprises the following steps:

[0010] (1) The following raw material components are mixed uniformly by weight to prepare a mixed material:

[0011]

[0012] Among them, PBAT and PLA totaled 100 copies.

[0013] The commercial antibacterial agent is at least one of polyhexamethyleneguanidine hydrochloride, ε-polylysine hydrochloride, and nisin;

[0014] (2) The mixture obtained in step (1) is subjected to sequential internal kneading, cutting, hot-pressing, and biaxial stretching to obtain a high-performance antibacterial and biodegradable PBAT-based composite film.

[0015] In this article, the Chinese name of PBAT in step (1) is polybutylene terephthalate-adipate, which is a thermoplastic biodegradable plastic. Conventional industrial PBAT raw materials in the field of this technology can be directly selected. Those skilled in the art can select a suitable PBAT grade according to specific needs and process requirements, or refer to the conventional PBAT grades in the application field of the final product.

[0016] In one of the technical solutions, the PBAT selected in step (1) includes any one of A400 from Zhuhai Jinfa Biomaterials Co., Ltd., TH801T from Xinjiang Blue Mountain Tunhe Chemical, and Ecoflex C1200 from BASF.

[0017] In this article, the Chinese name of PLA in step (1) is polylactic acid, which is a biodegradable material. Conventional industrial PLA raw materials in the field of this technology can be directly selected. Those skilled in the art can select a suitable PLA brand according to specific needs and process requirements, or refer to conventional PLA brands in the application field of the final product.

[0018] In one of the technical solutions, the PLA selected in step (1) includes any one of American NatureWorks 4032D / 4060D, Total L175, Hisun Bio REVODE110, and Fengyuan FY802.

[0019] It should be noted that, based on the PBAT / PLA blending system with PBAT as the main component and PLA as the reinforcing dispersed phase, due to the poor compatibility between PLA and PBAT, the large proportion of the third component such as processing aids / fillers added and blended can easily lead to further deterioration of the compatibility between the two, thereby causing the performance of the PBAT / PLA blended products to be significantly deteriorated. In order to solve the above problems, the inventors of the present invention found through comparative experiments in the early research and development work that when the cross-linking agent is selected as diisopropylbenzene peroxide (DCP), only a very small amount of DCP (0.05-0.15wt% of the PBAT / PLA blending system) is added to achieve the in-situ reaction of the two phases in the PBAT / PLA blending system at the interface through melt blending to generate new chemical bonds such as ester groups and ether bonds, replacing the weaker intermolecular forces such as van der Waals forces, and generating macromolecular chains similar to PLA-g-PBAT, thereby improving the compatibility between the two and improving the mechanical properties and barrier properties of the blended material. The present invention also adds a small amount of glycerol (3-5wt% of the PBAT / PLA blend system), which can separate the chain segments between PLA and PBAT molecules, improve the chain segment mobility, and enhance the compatibility between the two phases and the plasticity of the material. The above research and development work has maintained the performance of the PBAT / PLA blend system products as much as possible while minimizing the amount of processing aids added.

[0020] After determining through comparative tests that a lower amount of processing aid can basically solve the compatibility of the PBAT / PLA blend system, the inventors of the present invention attempted to further introduce an antibacterial agent to give the product antibacterial functionality, but found through experiments that in order to achieve a certain standard of antibacterial performance on the film product prepared after biaxial stretching, the use of a higher content (~10wt%) of commercial antibacterial agents will also lead to significant deterioration of the mechanical properties of the product.

[0021] Therefore, one of the important invention points of the present invention is that in the comparison test of the selection of commercial antibacterial agents, it was accidentally found that when the commercial antibacterial agent is selected as any one of polyhexamethyleneguanidine hydrochloride, ε-polylysine hydrochloride, and nisin, under the condition of lower addition amount (not more than 3wt% of the PBAT / PLA blend system), it not only has a certain standard of antibacterial performance, but also can significantly improve the mechanical properties of the film product finally prepared. Among them, when polyhexamethyleneguanidine hydrochloride is selected, it has a higher heat resistance and the antibacterial effect is better than ε-polylysine hydrochloride or nisin, but the inventor found that when the commercial antibacterial agent is selected as ε-polylysine hydrochloride and nisin, it is surprisingly found that the heat sealing strength, heat shrinkage rate, and oxygen permeability coefficient of the prepared film product have all increased significantly, especially the heat sealing strength performance, when ε-polylysine hydrochloride and nisin are used in combination, it is not only not reduced, but enhanced, which is completely beyond the expectations of the inventor.

[0022] Based on the above invention, in one of the technical solutions, the commercial antibacterial agents are ε-polylysine hydrochloride and nisin. In order to further improve the comprehensive performance of the film product finally prepared, it is further preferred that the mass ratio of ε-polylysine hydrochloride and nisin is 2:1.

[0023] Based on the above invention, in one of the technical solutions, the commercial antibacterial agent is polyhexamethyleneguanidine hydrochloride. In order to further reduce the amount of the commercial antibacterial agent added while ensuring that the prepared composite film has certain antibacterial properties, the amount of the polyhexamethyleneguanidine hydrochloride added is preferably 1 to 1.1 wt%.

[0024] In this article, the mixture described in step (2) is successively cut into blocks, hot-pressed and biaxially stretched after internal mixing, wherein the cutting into blocks after internal mixing, hot-pressed and biaxially stretched are all conventional processes / procedures for preparing film products from thermoplastic plastics, and because the added amounts of additives and antibacterial agents in the present invention are relatively lower, those skilled in the art can directly process according to common knowledge or conventional process parameters without the need for additional process conditions.

[0025] In order to better illustrate the present invention and provide a technical solution for reference, the mixed material in step (2) is cut into blocks, hot-pressed and biaxially stretched after banburying in sequence, wherein the process parameters of the banburying are: the temperature is set at 150-155°C and the rotation speed is 50-60r / min; the process parameters of the hot-pressed sheet are: the hot pressing temperature is set at 155-160°C, the pressure in the preheating stage is 0MPa and maintained for 2-3min, the pressure is adjusted to 2.5-3MPa for pre-pressing for 2-3min, then the pressure is increased to 8-12MPa and maintained for 4-5min, and the pressure is continued to be maintained for 2-5min after cooling to room temperature; the process parameters of biaxial stretching are: the stretching temperature is set at 90-110°C, preheating is 90-120s, heat setting is performed for 30-60s after stretching, the stretching speed is 15-75mm / s, and the longitudinal and transverse stretching ratios are each 2.5-4.

[0026] Based on the above technical solution for reference, the thickness of the prepared film product is 30 to 80 μm.

[0027] In this article, the mixing, cutting, etc. all follow the conventional principles in chemical processes, and those skilled in the art can perform specific operations based on common knowledge.

[0028] The high-performance antibacterial and degradable PBAT-based composite film prepared according to the present invention has application fields including food preservation, daily consumer product packaging, agricultural film, medical treatment, etc.

[0029] The present invention has the following beneficial effects:

[0030] (1) The technical solution provided by the present invention realizes that while improving the compatibility of the PBAT / PLA blend system, a smaller amount of processing aids can be added without affecting the mechanical properties, so as to further improve the various properties of the prepared film products and give full play to the advantages of the PBAT / PLA blend system.

[0031] (2) In the technical solution provided by the present invention, by selectively adding a smaller amount of commercial antimicrobial agent, the antimicrobial rate against Staphylococcus aureus can reach 99%, and the antimicrobial rate against Escherichia coli can reach 100% under the premise of a smaller addition amount; it is also surprisingly found that under the combined use of commercial antimicrobial agents, the heat sealing strength of the film product is significantly improved.

[0032] (3) The technical solution provided by the present invention is simple to prepare and low in cost. The film product obtained has good mechanical properties and antibacterial properties, and the oxygen barrier property of the film is better than that of polyethylene film products currently on the market. It is conducive to use in the field of green packaging and is expected to achieve industrial production, with good market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1The following are physical display diagrams of samples prepared in Examples 1, 5, 9, and 13 of the present invention. Among them, Figure (a) corresponds to Example 13; Figure (b) corresponds to Example 1; Figure (c) corresponds to Example 9; and Figure (d) corresponds to Example 5.

[0034] Figure 2 The schematic diagram of the gas barrier principle of the sample before and after biaxial stretching of Example 1 of the present invention is shown in the figure. In the figure, PBAT corresponds to the PBAT material before biaxial stretching, BOPBAT corresponds to the PBAT film after biaxial stretching, PBAT / PLA / PHMG corresponds to the sheet material in Example 1 before biaxial stretching, and BOPBAT / PLA / PHMG corresponds to the film sample in Example 1 after biaxial stretching.

[0035] Figure 3 The cross-sectional SEM electron microscope images and energy spectrum analysis diagrams of the intermediate sheets and final samples prepared in Comparative Example 1 and Examples 1 and 3 of the present invention are shown.

[0036] Figure 4 These are cross-sectional SEM images of the samples prepared in Examples 1, 5, and 21 of the present invention.

[0037] Figure 5 This is a comparative bar chart of the tensile strength and elongation at break of the samples prepared in Examples 1 to 16 of the present invention and Comparative Examples 1 to 4. DETAILED DESCRIPTION

[0038] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Although it is believed that those of ordinary skill in the art fully understand the following terms, the following definitions are still stated to help illustrate the subject matter disclosed by the present invention.

[0039] A method for preparing a high-performance antibacterial and degradable PBAT-based composite film based on biaxial stretching technology comprises the following steps:

[0040] (1) The following raw material components are mixed uniformly by weight to prepare a mixed material:

[0041]

[0042] Among them, PBAT and PLA totaled 100 copies.

[0043] The commercial antibacterial agent is at least one of polyhexamethyleneguanidine hydrochloride, ε-polylysine hydrochloride, and nisin;

[0044] (2) The mixture obtained in step (1) is subjected to sequential internal kneading, cutting, hot-pressing, and biaxial stretching to obtain a high-performance antibacterial and biodegradable PBAT-based composite film.

[0045] In this article, the Chinese name of PBAT in step (1) is polybutylene terephthalate-adipate, which is a thermoplastic biodegradable plastic. Conventional industrial PBAT raw materials in the field of this technology can be directly selected. Those skilled in the art can select a suitable PBAT grade according to specific needs and process requirements, or refer to the conventional PBAT grades in the application field of the final product.

[0046] In one embodiment, the PBAT selected in step (1) includes any one of A400 from Zhuhai Kingfa Biomaterials Co., Ltd., TH801T from Xinjiang Blue Mountain Tunhe Chemical, and Ecoflex C1200 from BASF.

[0047] In this article, the Chinese name of PLA in step (1) is polylactic acid, which is a biodegradable material. Conventional industrial PLA raw materials in the field of this technology can be directly selected. Those skilled in the art can select a suitable PLA brand according to specific needs and process requirements, or refer to conventional PLA brands in the application field of the final product.

[0048] In one embodiment, the PLA in step (1) is selected from any one of American NatureWorks 4032D / 4060D, Total L175, Hisun Bio REVODE110, and Fengyuan FY802.

[0049] In one embodiment, in step (1), the PBAT is 70 to 80 parts, such as 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts, 80 parts or any range or point value therebetween; the PLA is 20 to 30 parts, such as 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts or any range or point value therebetween; the dicumyl peroxide is 0.05 to 0.15 parts, for example, 0.05 parts, 0.06 parts, 0.07 parts, 0.08 parts, 0.09 parts, 0.10 parts, 0.11 parts, 0.12 parts, 0.13 parts, 0.14 parts, 0.15 parts or any range or point value therebetween; the glycerol is 3 to 5 parts, for example, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts or any range or point value therebetween; the commercial antibacterial agent is 0.5 to 3 parts, for example, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts or any range or point value therebetween.

[0050] It should be noted that, based on the PBAT / PLA blending system with PBAT as the main component and PLA as the reinforcing dispersed phase, due to the poor compatibility between PLA and PBAT, the large proportion of the third component such as processing aids / fillers added and blended can easily lead to further deterioration of the compatibility between the two, thereby causing the performance of the PBAT / PLA blended products to be significantly deteriorated. In order to solve the above problems, the inventors of the present invention found through comparative experiments in the early research and development work that when the cross-linking agent is selected as diisopropylbenzene peroxide (DCP), only a very small amount of DCP (0.05-0.15wt% of the PBAT / PLA blending system) is added to achieve the in-situ reaction of the two phases in the PBAT / PLA blending system at the interface through melt blending to generate new chemical bonds such as ester groups and ether bonds, replacing the weaker intermolecular forces such as van der Waals forces, and generating macromolecular chains similar to PLA-g-PBAT, thereby improving the compatibility between the two and improving the mechanical properties and barrier properties of the blended material. The present invention also adds a small amount of glycerol (3-5wt% of the PBAT / PLA blend system), which can separate the chain segments between PLA and PBAT molecules, improve the chain segment mobility, and enhance the compatibility between the two phases and the plasticity of the material. The above research and development work has maintained the performance of the PBAT / PLA blend system products as much as possible while minimizing the amount of processing aids added.

[0051] After determining through comparative tests that a lower amount of processing aid can basically solve the compatibility of the PBAT / PLA blend system, the inventors of the present invention attempted to further introduce an antibacterial agent to give the product antibacterial functionality, but found through experiments that in order to achieve a certain standard of antibacterial performance on the film product prepared after biaxial stretching, the use of a higher content (~10wt%) of commercial antibacterial agents will also lead to significant deterioration of the mechanical properties of the product.

[0052] Therefore, one of the important invention points of the present invention is that in the comparison test of the selection of commercial antibacterial agents, it was accidentally found that when the commercial antibacterial agent is selected as any one of polyhexamethyleneguanidine hydrochloride, ε-polylysine hydrochloride, and nisin, under the condition of lower addition amount (not more than 3wt% of the PBAT / PLA blend system), it not only has a certain standard of antibacterial performance, but also can significantly improve the mechanical properties of the film product finally prepared. Among them, when polyhexamethyleneguanidine hydrochloride is selected, it has a higher heat resistance and the antibacterial effect is better than ε-polylysine hydrochloride or nisin, but the inventor found that when the commercial antibacterial agent is selected as ε-polylysine hydrochloride and nisin, it is surprisingly found that the heat sealing strength, heat shrinkage rate, and oxygen permeability coefficient of the prepared film product have all increased significantly, especially the heat sealing strength performance, when ε-polylysine hydrochloride and nisin are used in combination, it is not only not reduced, but enhanced, which is completely beyond the expectations of the inventor.

[0053] Based on the above invention, in one embodiment, the commercial antibacterial agent is ε-polylysine hydrochloride and nisin. In order to further improve the comprehensive performance of the film product finally prepared, it is further preferred that the mass ratio of ε-polylysine hydrochloride and nisin is 2:1.

[0054] Based on the above invention, in one embodiment, the commercial antibacterial agent is polyhexamethyleneguanidine hydrochloride. In order to further reduce the amount of the commercial antibacterial agent added while ensuring that the prepared composite film has certain antibacterial properties, the amount of the polyhexamethyleneguanidine hydrochloride added is preferably 1 to 1.1 wt%.

[0055] In this article, the mixture described in step (2) is successively cut into blocks, hot-pressed and biaxially stretched after internal mixing, wherein the cutting into blocks after internal mixing, hot-pressed and biaxially stretched are all conventional processes / procedures for preparing film products from thermoplastic plastics, and because the added amounts of additives and antibacterial agents in the present invention are relatively lower, those skilled in the art can directly process according to common knowledge or conventional process parameters without the need for additional process conditions.

[0056] In order to better illustrate the present invention and provide an implementation method for reference, the mixed material in step (2) is cut into blocks, hot-pressed and biaxially stretched after internal mixing, wherein the process parameters of the internal mixing are: the temperature is set at 150-155°C and the rotation speed is 50-60r / min; the process parameters of the hot-pressed sheet are: the hot pressing temperature is set at 155-160°C, the pressure in the preheating stage is 0MPa and maintained for 2-3min, the pressure is adjusted to 2.5-3MPa for pre-pressing for 2-3min, then the pressure is increased to 8-12MPa and maintained for 4-5min, and the pressure is continued to be maintained for 2-5min after cooling to room temperature; the process parameters of biaxial stretching are: the stretching temperature is set at 90-110°C, preheating is 90-120s, heat setting is 30-60s after stretching, the stretching speed is 15-75mm / s, and the longitudinal and transverse stretching ratios are 2.5-4 respectively.

[0057] Based on the above reference implementation method, the thickness of the prepared film product is 30 to 80 μm.

[0058] In this article, the mixing, cutting, etc. all follow the conventional principles in chemical processes, and those skilled in the art can perform specific operations based on common knowledge.

[0059] The present invention will be further explained in detail with reference to the following examples. However, it should be understood by those skilled in the art that these examples are provided for illustrative purposes only and are not intended to limit the present invention.

[0060] Example

[0061] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. The specific conditions not specified in the examples are carried out according to the conditions recommended by normal conditions or manufacturers. The reagents used or the instruments not specified by the manufacturer are all conventional products that can be obtained commercially. The application should not be construed as being limited to the specific examples described.

[0062] 1. Raw materials

[0063] PBAT: TH801T, Xinjiang Blue Mountain Tunhe Chemical Co., Ltd.;

[0064] PLA: American NatureWorks 4060D;

[0065] Dicumyl peroxide: Anhui Xiangyun Rubber & Plastic Co., Ltd.

[0066] Glycerol: Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0067] ε-Poly-lysine hydrochloride: Zhejiang New Silver Elephant Bioengineering Co., Ltd.;

[0068] Nisin: Shandong Yuantai Bioengineering Co., Ltd.

[0069] Polyhexamethyleneguanidine hydrochloride: Shanghai Aladdin Biochemical Technology Co., Ltd.

[0070] 2. Preparation method

[0071] A method for preparing a high-performance antibacterial and degradable PBAT-based composite film based on biaxial stretching technology comprises the following steps:

[0072] (1) The following raw material components are mixed uniformly by weight to prepare a mixed material:

[0073]

[0074] Among them, PBAT and PLA totaled 100 copies.

[0075] The commercial antibacterial agent is at least one of polyhexamethyleneguanidine hydrochloride, ε-polylysine hydrochloride, and nisin;

[0076] (2) the mixture obtained in step (1) is subjected to sequential internal kneading, cutting, hot pressing, and biaxial stretching to obtain a high-performance antibacterial and biodegradable PBAT-based composite film;

[0077] The process parameters of the banburying are: the temperature is set at 150°C and the speed is 50r / min;

[0078] The process parameters of the hot pressing casting sheet are as follows: the hot pressing temperature is set to 160°C, the pressure in the preheating stage is 0MPa and maintained for 3min, the pressure is adjusted to 3MPa for pre-pressing for 2min, then the pressure is increased to 10MPa and maintained for 5min, and the pressure is continued to be maintained for 2min after cooling to room temperature;

[0079] The process parameters of the biaxial stretching are: the stretching temperature is set at 110° C., preheating is 120 seconds, heat setting is 30 seconds after stretching, the stretching speed is 15 mm / s, and the longitudinal and transverse stretching ratios are 2.5 to 4 respectively.

[0080] 3. Test methods

[0081] (1) Tensile strength and elongation at break

[0082] The mechanical properties of sheet materials and biaxially oriented films were tested using an Instron 5567 universal material testing machine (Instron, USA). The film samples were cut into dumbbell-shaped specimens using a custom mold, with a test width of 4 mm and a test length of 27 mm. The tensile machine was stretched at a speed of 50 mm / min during the test.

[0083] (2) Oxygen barrier properties

[0084] The oxygen barrier properties of the biaxially oriented films were tested using a VAC-V1 permeability tester (Jinan Languang Electromechanical Technology Co., Ltd.).

[0085] The biaxially oriented film is cut into circular specimens with a diameter of 60 mm, and the permeation cavity is separated into two independent spaces. To prevent gas penetration, vacuum grease is applied to the permeation cavity to seal it. First, both sides of the specimen are evacuated to a vacuum, and then 0.1 MPa of test gas is filled into one side, while the other side is kept in a vacuum state, forming a 0.1 MPa test gas pressure difference on both sides of the specimen. At 40°C and 50% humidity, the test gas penetrates through the film into the low-pressure side and causes a change in the pressure on the low-pressure side. The change in the pressure on the low-pressure side is measured with a high-precision sensor to obtain the oxygen permeability of the film.

[0086] (3) Heat sealing performance

[0087] The film was heat-sealed using a hand-pressed sealer (No. 16495, Deli Group Co., Ltd.), and the sealing strength of the film was tested using an Instron 5567 universal material testing machine (Instron Corporation, USA).

[0088] The film was heat-sealed for 4.5 seconds at a power of 140 W, and the heat-sealed sample was cut into 15 mm wide strips to be tested. The heat-sealing strength was tested with a universal material testing machine in N / 15 mm. Five parallel tests were performed to obtain the average value of the results.

[0089] (4) Thermal shrinkage test

[0090] A film sample cut into 100 mm × 100 mm was placed in an oil bath at 100°C and taken out after 20 seconds. The dimensions of the film in the longitudinal and transverse directions were measured after the film was cooled.

[0091] Thermal shrinkage = [(L0-L) / L0] × 100%

[0092] Where L0 is the size of the sample before oil bath heating, and L is the size of the sample after oil bath heating. Three samples were set for each sample, and the results were averaged.

[0093] (5) Antibacterial properties

[0094] The antibacterial activity of the film was tested by co-culture and plate count. The E. coli solution was diluted to 10 5 CFU / mL, dilute the Staphylococcus aureus solution to 10 7CFU / mL, add 50μL of diluted bacterial solution to the 6mm circular sample. Place in a 37℃ constant temperature incubator and culture for 4h. After the culture is completed, add 5mL PBS to elute, then use sterile PBS solution to dilute the bacterial solution 10 times continuously, take 100μL of the dilution and evenly spread it on the LB solid culture medium. Place in a 37℃ constant temperature incubator and culture for 18h, take out and take pictures and record the number of colonies.

[0095] Antibacterial rate = (1-C / C0) × 100%

[0096] Where C is the concentration of the experimental group's bacterial solution, and C0 is the concentration of the control group's bacterial solution. Three samples were set for each, and the results were averaged.

[0097] Example 1

[0098] Example 1 refers to the above "2. Preparation method" to prepare a high-performance antibacterial and degradable PBAT-based composite film as a sample for testing, wherein the commercial antibacterial agent is polyhexamethyleneguanidine hydrochloride, and the addition amount is 2 parts, and the longitudinal and transverse stretching ratios are 3.5 (3.5×3.5) respectively.

[0099] Example 2

[0100] Example 2 refers to the above "2. Preparation method" to prepare a high-performance antibacterial and degradable PBAT-based composite film as a sample for testing, wherein the commercial antibacterial agent is polyhexamethyleneguanidine hydrochloride, and the addition amount is 1.5 parts, and the longitudinal and transverse stretching ratios are 3.5 (3.5×3.5) respectively.

[0101] Example 3

[0102] Example 3 refers to the above "2. Preparation method" to prepare a high-performance antibacterial and degradable PBAT-based composite film as a sample for testing, wherein the commercial antibacterial agent is polyhexamethyleneguanidine hydrochloride, and the addition amount is 1 part, and the longitudinal and transverse stretching ratios are 3.5 (3.5×3.5) respectively.

[0103] Example 4

[0104] Example 4 refers to the above "2. Preparation method" to prepare a high-performance antibacterial and degradable PBAT-based composite film as a sample for testing, wherein the commercial antibacterial agent is polyhexamethyleneguanidine hydrochloride, and the addition amount is 0.5 parts, and the longitudinal and transverse stretching ratios are 3.5 (3.5×3.5) respectively.

[0105] Example 5

[0106] Example 5 refers to the above "2. Preparation method" to prepare a high-performance antibacterial and degradable PBAT-based composite film as a sample for testing, wherein the commercial antibacterial agent is polyhexamethyleneguanidine hydrochloride, and the addition amount is 2 parts, and the longitudinal and transverse stretching ratios are 4.5 (4.5×4.5) respectively.

[0107] Example 6

[0108] Example 6 refers to the above "2. Preparation method" to prepare a high-performance antibacterial and degradable PBAT-based composite film as a sample for testing, wherein the commercial antibacterial agent is polyhexamethyleneguanidine hydrochloride, and the addition amount is 1.5 parts, and the longitudinal and transverse stretching ratios are 4.5 (4.5×4.5) respectively.

[0109] Example 7

[0110] Example 7 refers to the above "2. Preparation method" to prepare a high-performance antibacterial and degradable PBAT-based composite film as a sample for testing, wherein the commercial antibacterial agent is polyhexamethyleneguanidine hydrochloride, and the addition amount is 1 part, and the longitudinal and transverse stretching ratios are 4.5 (4.5×4.5) respectively.

[0111] Example 8

[0112] Example 8 refers to the above "2. Preparation method" to prepare a high-performance antibacterial and degradable PBAT-based composite film as a sample for testing, wherein the commercial antibacterial agent is polyhexamethyleneguanidine hydrochloride, and the addition amount is 0.5 parts, and the longitudinal and transverse stretching ratios are 4.5 (4.5×4.5) respectively.

[0113] Example 9

[0114] Example 9 refers to the above "2. Preparation method" to prepare a high-performance antibacterial and degradable PBAT-based composite film as a sample for testing, wherein the commercial antibacterial agent is polyhexamethyleneguanidine hydrochloride, and the addition amount is 2 parts, and the longitudinal and transverse stretching ratios are 4 (4×4) each.

[0115] Example 10

[0116] Example 10 is a high-performance antibacterial and degradable PBAT-based composite film prepared by referring to the above "2. Preparation method" as a sample for testing, wherein the commercial antibacterial agent is polyhexamethyleneguanidine hydrochloride, and the addition amount is 1.5 parts, and the longitudinal and transverse stretching ratios are 4 (4×4) each.

[0117] Embodiment 11

[0118] Example 11 refers to the above "2. Preparation method" to prepare a high-performance antibacterial and degradable PBAT-based composite film as a sample for testing, wherein the commercial antibacterial agent is polyhexamethyleneguanidine hydrochloride, and the addition amount is 1 part, and the longitudinal and transverse stretching ratios are 4 (4×4) each.

[0119] Example 12

[0120] Example 12 refers to the above "2. Preparation method" to prepare a high-performance antibacterial and degradable PBAT-based composite film as a sample for testing, wherein the commercial antibacterial agent is polyhexamethyleneguanidine hydrochloride, and the added amount is 0.5 parts, and the longitudinal and transverse stretching ratios are 4 (4×4) each.

[0121] Example 13

[0122] Example 13 refers to the above "2. Preparation method" to prepare a high-performance antibacterial and degradable PBAT-based composite film as a sample for testing, wherein the commercial antibacterial agent is polyhexamethyleneguanidine hydrochloride, and the addition amount is 2 parts, and the longitudinal and transverse stretching ratios are 3 (3×3) each.

[0123] Embodiment 14

[0124] Example 14 refers to the above-mentioned "2. Preparation method" to prepare a high-performance antibacterial and degradable PBAT-based composite film as a sample for testing, wherein the commercial antibacterial agent is polyhexamethyleneguanidine hydrochloride, and the addition amount is 1.5 parts, and the longitudinal and transverse stretching ratios are 3 (3×3) each.

[0125] Embodiment 15

[0126] Example 15 is a high-performance antibacterial and degradable PBAT-based composite film prepared by referring to the above "2. Preparation method" as a sample for testing, wherein the commercial antibacterial agent is polyhexamethyleneguanidine hydrochloride, and the addition amount is 1 part, and the longitudinal and transverse stretching ratios are 3 (3×3) each.

[0127] Example 16

[0128] Example 16 refers to the above "2. Preparation method" to prepare a high-performance antibacterial and degradable PBAT-based composite film as a sample for testing, wherein the commercial antibacterial agent is polyhexamethyleneguanidine hydrochloride, and the added amount is 0.5 parts, and the longitudinal and transverse stretching ratios are 3 (3×3) each.

[0129] Embodiment 17

[0130] Example 17 refers to the above-mentioned "2. Preparation method" to prepare a high-performance antibacterial and degradable PBAT-based composite film as a sample for testing, wherein the commercial antibacterial agent is ε-polylysine hydrochloride, and the addition amount is 3 parts, and the longitudinal and transverse stretching ratios are 3.5 (3.5×3.5) respectively.

[0131] Embodiment 18

[0132] Example 18 refers to the above "2. Preparation method" to prepare a high-performance antibacterial and degradable PBAT-based composite film as a sample for testing, wherein the commercial antibacterial agent is ε-polylysine hydrochloride and nisin in combination with a mass ratio of 2:1, a total addition amount of 3 parts, and the longitudinal and transverse stretching ratios are 3.5 (3.5×3.5) each.

[0133] Embodiment 19

[0134] Example 19 refers to the above "2. Preparation method" to prepare a high-performance antibacterial and degradable PBAT-based composite film as a sample for testing, wherein the commercial antibacterial agent is ε-polylysine hydrochloride and nisin in combination with a mass ratio of 1:2, a total addition amount of 3 parts, and the longitudinal and transverse stretching ratios are 3.5 (3.5×3.5) each.

[0135] Embodiment 20

[0136] Example 20 is a high-performance antibacterial and degradable PBAT-based composite film prepared by referring to the above “2. Preparation method” as a sample for testing, wherein the commercial antibacterial agent is nisin, and the addition amount is 3 parts, and the longitudinal and transverse stretching ratios are 3.5 (3.5×3.5) respectively.

[0137] Embodiment 21

[0138] Example 21 refers to the above "2. Preparation method" to prepare a high-performance antibacterial and degradable PBAT-based composite film as a sample for testing, wherein the commercial antibacterial agent is polyhexamethyleneguanidine hydrochloride, and the added amount is 2 parts, and the longitudinal and transverse stretching ratios are 1 (1×1) each.

[0139] Comparative Example 1

[0140] Comparative Example 1 is a degradable PBAT-based composite film prepared with reference to the above “2. Preparation method” without adding a commercial antibacterial agent as a comparative sample for testing. No commercial antibacterial agent was added during the preparation process, and the longitudinal and transverse stretching ratios were 3.5 (3.5×3.5) respectively.

[0141] Comparative Example 2

[0142] Comparative Example 2 is a biodegradable PBAT-based composite film prepared with reference to the above “2. Preparation method” without adding a commercial antibacterial agent as a comparative sample for testing. No commercial antibacterial agent was added during the preparation process, and the longitudinal and transverse stretching ratios were 4.5 (4.5×4.5) respectively.

[0143] Comparative Example 3

[0144] Comparative Example 3 is a degradable PBAT-based composite film prepared with reference to the above “2. Preparation method” without adding a commercial antibacterial agent as a comparative sample for testing. No commercial antibacterial agent was added during the preparation process, and the longitudinal and transverse stretching ratios were 4 (4×4) each.

[0145] Comparative Example 4

[0146] Comparative Example 4 is a degradable PBAT-based composite film prepared with reference to the above “2. Preparation method” without adding a commercial antibacterial agent as a comparative sample for testing. No commercial antibacterial agent was added during the preparation process, and the longitudinal and transverse stretching ratios were 3 (3×3) each.

[0147] 4. Test results

[0148] Table 1 Performance comparison table

[0149]

[0150] As shown in Table 1, after the introduction of polyhexamethylene lysine hydrochloride / ε-polylysine hydrochloride / nisin, the film still maintained good mechanical properties. When the cationic polymer antimicrobial agents (polyhexamethylene lysine hydrochloride, ε-polylysine hydrochloride) were added alone, they showed a certain enhancement effect, and the tensile strength of the film was improved. The polyhexamethylene lysine hydrochloride system and the ε-polylysine hydrochloride / nisin blend system helped to improve the barrier properties of the film, and when ε-polylysine hydrochloride or nisin was added alone, the oxygen permeability coefficient was improved. In addition, when the biaxial stretching ratio was increased, the molecular chain orientation was promoted, and the barrier properties of the film were improved. At the same time, the polyhexamethylene lysine hydrochloride system, ε-polylysine hydrochloride / nisin blend system, and nisin system all contribute to the improvement of the heat sealing strength of the film. The polyhexamethylene lysine hydrochloride system is more significant at a lower addition amount. When 2w% is added and the film stretching ratio is 3.5×3.5, the film heat sealing strength reaches more than 16.5N; and when 2w% ε-polylysine hydrochloride and 1w% nisin are added, the film has the best film heat sealing strength, which can reach more than 18N. The introduction of the system antibacterial agent and the biaxial stretching processing method have little effect on the thermal shrinkage rate of the film, which is conducive to the application of the prepared PBAT-based film in the field of heat shrinkable film. When 2w% ε-polylysine hydrochloride and 1w% nisin are added, the film has the best antibacterial performance, the antibacterial rate of Staphylococcus aureus is greater than 99.9%, and the antibacterial rate of Escherichia coli reaches 100%. However, when the addition amount of polyhexamethylene lysine hydrochloride is 1w%, the antibacterial rate of Staphylococcus aureus reaches 100%, and the antibacterial rate of Escherichia coli is >99%, which has a more efficient antibacterial performance.

[0151] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a high-performance antibacterial and degradable PBAT-based composite film based on biaxial stretching technology, characterized in that The following steps are involved: (1) The following raw material components are mixed uniformly by weight to prepare a mixed material: The commercial antibacterial agent is at least one of polyhexamethyleneguanidine hydrochloride, ε-polylysine hydrochloride, and nisin; (2) The mixture obtained in step (1) is subjected to sequential internal kneading, cutting, hot-pressing, and biaxial stretching to obtain a high-performance antibacterial and biodegradable PBAT-based composite film.

2. The method according to claim 1, characterized in that: The PBAT selected in step (1) includes any one of A400 from Zhuhai Jinfa Biomaterials Co., Ltd., TH801T from Xinjiang Blue Mountain Tunhe Chemical, and Ecoflex C1200 from BASF.

3. The method according to claim 1, characterized in that: The PLA selected in step (1) includes any one of American NatureWorks 4032D / 4060D, Total L175, Hisun Bio REVODE110, and Fengyuan FY802.

4. The method according to claim 1, characterized in that: The commercial antibacterial agents in step (1) are ε-polylysine hydrochloride and nisin, and the mass ratio of ε-polylysine hydrochloride to nisin is 2:

1.

5. The method according to claim 1, characterized in that: The commercial antibacterial agent in step (1) is polyhexamethyleneguanidine hydrochloride, and the addition amount of the polyhexamethyleneguanidine hydrochloride is 1 to 1.1 wt %.

6. The method according to claim 1, characterized in that: The mixed material in step (2) is successively cut into blocks, hot-pressed and biaxially stretched after being kneaded, wherein the kneading process parameters are: the temperature is set at 150-155°C and the rotation speed is 50-60r / min.

7. The method according to claim 1, characterized in that: The mixed material in step (2) is successively cut into blocks, hot-pressed and biaxially stretched after internal mixing, wherein the process parameters of the hot-pressed sheet are as follows: the hot-pressing temperature is set at 155-160°C, the pressure in the preheating stage is 0 MPa and maintained for 2-3 min, the pressure is adjusted to 2.5-3 MPa for pre-pressing for 2-3 min, then the pressure is increased to 8-12 MPa and maintained for 4-5 min, and the pressure is continued to be maintained for 2-5 min after cooling to room temperature.

8. The method according to claim 1, characterized in that: The mixed material in step (2) is successively cut into blocks, hot-pressed and biaxially stretched after internal mixing, wherein the process parameters of the biaxial stretching are: the stretching temperature is set to 90-110°C, preheating is 90-120s, heat setting is performed for 30-60s after stretching, the stretching speed is 15-75mm / s, and the longitudinal and transverse stretching ratios are 2.5-4 respectively.

9. The high-performance antibacterial and degradable PBAT-based composite film prepared by the method for preparing a high-performance antibacterial and degradable PBAT-based composite film based on biaxial stretching technology as claimed in claim 1.

10. Application of the high-performance antibacterial and degradable PBAT-based composite film as claimed in claim 9 in the field of packaging materials.

Citation Information

Cited By

  • Antibacterial film material and preparation method thereof

    CN120795588A

  • Antibacterial film material and method for preparing the same

    CN120795588B